IMPLEMENTASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM PENGELOLAAN KEUANGAN DESA DI DESA LUBUK SAKAT KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR TAHUN 2024 - Iffan Putra Defizon; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The implementation of Siskeudes in village financial management still faces various constraints, including technical and institutional challenges, particularly related to village officials’ understanding of the use of the Siskeudes application and the availability of human resources. This study aims to analyze the implementation of Siskeudes in village financial management as well as the factors influencing it. The research refers to the provisions of laws and regulations, particularly the Regulation of the Minister of Home Affairs (Permendagri) Number 20 of 2018 concerning Village Financial Management. The research method employed is a descriptive qualitative approach, with data collection techniques conducted through interviews and documentation. Data analysis is carried out through data reduction, data presentation, and conclusion drawing or verification. The research was conducted in Lubuk Sakat Village, Perhentian Raja District, Kampar Regency. The results of the study indicate that the implementation of Siskeudes in village financial management at the stages of planning, implementation, administration, reporting, and accountability has generally been carried out, but has not yet been fully optimal. The use of Siskeudes in financial management still encounters obstacles limited understanding due to changes in application versions, and technical issues such as network problems. The factors influencing the implementation of Siskeudes include communication, which has been fairly effective; limited resources and insufficient understanding among village officials; the disposition or attitude of implementers, which is relatively positive; and a bureaucratic structure that does not yet support an optimal division of labor. Keywords: Implementation of Siskeudes, Financial Management, Village Government